2015
DOI: 10.1002/pssr.201510318
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered Zn(O,S)/In2O3:H window layers for enhanced blue response of chalcopyrite solar cells

Abstract: A combination of undoped ZnO and ZnO:Al is the most commonly used window layer stack for chalcopyrite solar cells. The high carrier density and thickness required to achieve a sufficiently low sheet resistance lead to optical absorption and cause losses in photocurrent, in particular in monolithically interconnected modules. Additionally, the band gap of the CdS buffer layer and of un‐doped ZnO limit the blue response. These losses could be avoided by using a transparent conductive oxide with high carrier mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…We have, however, made some curious observations in our experiments, which cannot be easily explained. Thus, the In 2 O 3 :H 2 O films (state II in the Table 1) grow predominantly X-ray crystalline on such substrates like molybdenum-films, i -ZnO, Si-wafer, or CIGS-absorber [11]. Moreover, if any additional oxygen is injected into the sputtering gas, the films becomew crystalline and resistive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, however, made some curious observations in our experiments, which cannot be easily explained. Thus, the In 2 O 3 :H 2 O films (state II in the Table 1) grow predominantly X-ray crystalline on such substrates like molybdenum-films, i -ZnO, Si-wafer, or CIGS-absorber [11]. Moreover, if any additional oxygen is injected into the sputtering gas, the films becomew crystalline and resistive.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies revealed the effect of oxygen addition to the sputter-gas on the In 2 O 3 :H crystallisation progress [11]. However, the question of whether we deal with so-called plasma damage still remains.…”
Section: Introductionmentioning
confidence: 99%
“…(1) to achieve higher conductivities while circumventing this trade-off between transparency and conductivity. Compared to ITO, the l of hydrogenated indium oxide (IO:H) films is greater by a factor of 3-4, 6,7 allowing improved nIR transparency without decreasing r. This allows for high performance in a wide range of photovoltaic a) devices, such as Cu(In,Ga)Se 2 solar cells, [8][9][10] perovskite solar cells, 11,12 and SHJ solar cells. 5,[13][14][15] However, the root cause of improved l in IO:H is not fully understood and thus motivates this current study.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the greatly-reduced IR-losses in such TCOs, they have found direct application in various solar cell devices, mainly leading to increased short-circuit current densities Jsc when compared to conventional ITO. For example, these high-mobility TCOs have played a key role in achieving the record conversion efficiencies for silicon heterojunction (SHJ) solar cells 8,9 , and are also being explored for CIGS [10][11][12] and perovskite tandem cells. 13,14,15 Among these high-mobility TCOs, In2O3:H is capable of achieving the highest mobility with values even up to 138 cm 2 /Vs.…”
Section: Introductionmentioning
confidence: 99%